Initial Gelogical Maps of the AC-H-10 Rongo and AC-H-15 Zadeni Quadrangles of Ceres using DAWN spacecraft data - Platz, Thomas; Nathues, Andreas; Crown, David; Mest, Scott Charles; Williams, David; Hoffmann, Martin; Schäfer, Michael; Sizemore, Hanna; Ruesch, Ottaviano; Preusker, Frank (2015)
We used geologic mapping applied to Dawn spacecraft data as a tool to understand the geologic history of the Ac-H-10 Rongo and Ac-H-15 Zadeni quadrangles of dwarf planet Ceres. These regions, Rongo and Zadeni, are located between 22°S-22°N and 288°-360°E and 65-90°S and 0°-360°E, respectively. The Rongo Quadrangle hosts a number of features: 1) the southwest portion is dissected by curvilinear structures likely caused by Yalode basin formation; 2) the central part is marked by dome-like constructs up to 100 km across; 3) a peculiar bright, c.4 km tall, conical structure informally known as the ‘pyramid’; 4) impact craters of various diameters appear moderately to highly degraded or are partially buried; and 5) bright material is primarily exposed in the central portion and often associated with craters. Rongo crater (68 km across) exhibits a central peak and scalloped walls indicative of its degraded appearance. The Zadeni Quadrangle is characterised by impact craters up to 130 km in diameter of which Zadeni crater is the largest. Impact craters across all sizes exhibit fresh to highly degraded morphologies or are partially buried. Many craters developed central peaks. Inter-crater plains are generally hummocky with isolated regions of smooth-textured surfaces. The south pole area (85-90°S) is poorly illuminated and may host a large impact structure. Upcoming work includes compositional assessment of surface units utilising FC colour images and VIR spectral data and establishment of relative and absolute stratigraphy using crater-based dating techniques.